COVID-19: Crisis Management and Promethean Thinking in Digital Age - Heimo OI; Heimo J; Hakkala A (Germany, 2022)
Abstract. In this paper we discuss the current COVID-19 crisis, digital rights, trust as part of the society and thinking ahead with the future crisis. As the pandemic has given us various examples around the world on what options we have in battling with this deadly disease and will eventually give us large amount of data on what of the various different methods seemed effective. Yet we should also focus on what is the ethical way for promoting individual rights and social cohesion before the next eventual crisis hits the globe. Keywords: COVID-19, Coronavirus, Digitalization, Ethics, Information technology, Information security
Proceedings of the Conference on Technology Ethics, Turku, Finland, October, 21, 2020